Endothelial Cell Injury Caused by Candida albicans Is Dependent on Iron - Fratti, Rutilio A. (American Society for Microbiology, 1998)
Although it is known that Candida albicans causes endothelial cell injury, in vitro and in vivo, the mechanism by which this process occurs remains unknown. Iron is critical for the induction of injury in many types of host cells. Therefore, we investigated the role of iron in Candida-induced endothelial cell injury. We found that pretreatment of endothelial cells with the iron chelators phenanthroline and deferoxamine protected them from candidal injury, even though the organisms germinated and grew normally. Loading endothelial cells with iron reversed the cytoprotective effects of iron chelation. Moreover, chelation of endothelial cell iron significantly reduced phagocytosis of C. albicans by these cells, while candidal adherence to chelator-treated endothelial cells was slightly enhanced. Since endothelial cell phagocytosis of C. albicans is required for endothelial cell injury to occur, inhibition of phagocytosis is likely the principal mechanism of the cytoprotective effects of iron chelation. The production of toxic reactive oxygen intermediates by host cells is known to be inhibited by iron chelation. Therefore, we investigated whether treating endothelial cells with antioxidants could mimic the cytoprotective effects of iron chelation. Neither extracellular nor membrane-permeative antioxidants reduced candidal injury of endothelial cells. Furthermore, depleting endothelial cells of the endogenous antioxidant glutathione did not render them more susceptible to damage by C. albicans. These results suggest that candidal injury of endothelial cells is independent of the production of reactive oxygen intermediates and that the cytoprotective effects of iron chelation are not due to inhibition of the synthesis of these toxic intermediates.